القيمة التربوية في كتاب المحفوظات الموضوعية عن العلم والأدب لإبن عارف - N Nuha; M. Syakirin Ghozaly (Universitas Muhammadiyah Surakarta, 2020)
The aim of this research is to find a general description of the mahfudzat thematic book of the Arabic proverb, the science and manners written by Ibn Arief, and to know the educational values contained in the book. Literary study and conceptual models, content analysis and analytical, inductive and normative approaches are used in this research methodology. The key source of data is Ibn Arief’s book on mahfudzat. The conclusion of this is 1. That the general description of the book of mahfudzat written by ibn arif is that the contents of the book of mahfudzat include al-hadith and atsar companions, verses of wisdom, advice of scholars and poets. The contents of the discussion in this book begin with a broad theme of teaching advice, in the middle of the book they discuss different kinds of Arabic proverbs, Mahfudzat and its principles, and end with practice exercises. The essence of the Mahfudzat discussion in this book consists of three chapters. The first chapter deals with science, the second chapter on manners, and the third chapter on manners. The total amount of mahfudzat in the book is 92. 2. The education principles in the book of Mahfudzat include five (five) elements of education meaningfully: religious education, science, charity, moral and social education. 1. The importance of religious education is intended to encourage people to improve their faith and to cleanse their lives forever. 2. The importance of scientific education is aimed at maintaining human dignity, becoming a decent individual and helping others 3. Amalyah education interest, strives to educate people so that lives are more successful and deserving of worship, are always behaving and thinking positively. 4. Moral education interest, aims to educate people that they are cautious, iffah, izzah, modest, and 5. The value of social education, aims to educate humans to always establish communication with others, because the many relationships are one way to facilitate the arrival of sustenance.